The Effect of Macroeconomic Indicators on Collection of Zakat, Infaq, and Alms (ZIS): A Case of the National Zakat Amil Agency (BAZNAS) in Java 2013-2020 - Abdullah Abdullah; Abdul Qoyum (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2022)
Indonesia is the largest Muslim country in the world with a Muslim population of 229 million people and ZIS collection institutions such as BAZNAS and LAZIS have spread throughout the archipelago. This research aims to determine how much influence the variables have in increasing the collection of Zakat, Infaq, and Alms (ZIS) in BAZNAS throughout the Province of Java. The variables used to explain the effect of macroeconomic variables on the collection of Zakat, Infaq, and Alms at BAZNAS are Regional Minimum Wages, Inflation, Per capita Income and Unemployment by using secondary data collection techniques or directly on the BAZNAS official website per year. This study uses the Common Effect Model (CEM) analysis model on panel data regression using time series and cross section data for the years 2013-2020.The results of this study indicate that of all independent variables that can affect ZIS income, only inflation and per capita income variables, while the Provincial Minimum Wage and Unemployment variables have no effect on the dependent variable.